An Improved Three-Level Full-Bridge Soft-Switching DC/DC Converter with Wide Load Range for Energy Storage System - Narongrit Sanajit; Anuwat Jangwanitlert (International Review of Electrical Engineering (IREE), 2024)
This article aims to present an improved three-level full-bridge (3L-FB) DC/DC converter in which all switches can operate under soft-switching conditions for a wide load range. It is suitable for applications with high input voltage and input power. The proposed circuit has some interesting features: the voltage across the switch is only half of the input voltage. The phase-shifted switching pattern is used for the output voltage control. Furthermore, auxiliary inductors are added to the circuit to verify that the main switches are operating under the soft switching condition for a wide load range, particularly light load scenarios. And clamping diodes can also facilitate in achieving the soft switching condition, leading to improved performance by lowering the loss of semiconductor devices in the circuit. The proposed three-level full-bridge (3L-FB) DC/DC converter circuit has been designed and simulated, and the results of the prototype test at 2.5 kW of output power rating have been analyzed to confirm the performance of the proposed circuit.
Keywords: Multilevel Inverters and Converters; Advanced DC-DC Converters; Microgrid Control and Optimization